The Influence of Digital Marketing on Repurchase Intention with Consumer Satisfaction as an Intervening Variable in Oh My Skin Products - Najah Nur Syahirah; Ratna Kusumawati (Faculty of Economics and Business, Universitas Wahid Hasyim, 2024)
This research aims to analyze the influence of digital marketing on repurchase interest through consumer satisfaction as an intervening variable for oh my skin products. The population in this research are consumers who have purchased Oh My Skin products more than once or repeatedly. The data collection method is by distributing questionnaires and taking samples using the Lemeshow formula, namely 96 respondents and rounded up to 100 respondents. Data processing uses a Structural Equation Modeling approach with the help of the SmartPLS 4.0 program. The research results show that Digital Marketing has a positiveand significant effect on repurchase interest, digital marketing has a significant positive effect on consumer satisfaction, consumer satisfaction has a positive and significant effect on repurchase interest, Consumer Satisfaction Variable, can mediate between the Digital Marketing Variable and Repurchase Intention. Companies are expected to be able to increase product marketing through digital marketing because it has been proven to help increase customer satisfaction and repurchase interest.